Strategia rozwoju systemów teleinformatycznych krajowego systemu ratowniczo-gaśniczego - Sobieraj, Grzegorz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The strategy of development of ICT systems in alerting the local society is an important element of planning and management of the civil defense of the country. How to carefully plan the development of systems that will enable proper alerting? What public alert systems are effective and what should be modernized? The development strategy attempts to answer the questions about the direction in which it is necessary to go, that the alerting should be based on proven telecommunications systems, but also be adapted to the rapidly growing Polish society.
Keywords: telekomunikacja; system alarmowy; strategia; społeczności lokalne